Peacebuilding in language education : innovations in theory and practice - Oxford, Rebecca L.; Gregersen, Tammy (Bristol ; Blue Ridge Summit : Multilingual Matters, 2021)
"This book shares wisdom and strategies to help language teachers, teacher educators, and peace educators communicate peace, contribute to peace and weave peacebuilding into classrooms and daily life. The book's Language of Peace Approach and more than 50 creative activities nurture peacebuilding skills in students, educators and the community"--
Frontmatter -- Contents -- Tables and Figures -- Dedications and Acknowledgments -- Contributors -- Foreword -- Gregory Hadley -- Section I Language Education Responds to the Call for Peace -- 1 The Call for Peace in Language Education: This Book's Purpose, Themes and Peace Approach -- 2 Empowering Language Teachers to Be Influential Peacebuilders: Knowledge, Competencies and Activities -- 3 The Nonverbal Channels of Peacebuilding: What Teachers, Trainers and Facilitators Need to Know -- Section II: Applying Peacebuilding for Inner, Interpersonal and Intergroup Peace -- 4 Inner Peace and Emotion Regulation during Oral Production in ESL/EFL Teacher Education -- 5 How Increased Self-regulation, Learner Autonomy and Learner Cooperation Raise Self-esteem and Consequently Inner Peace and Interpersonal Peace: Insights from an Innovative School Context -- 6 Revolutionary Love and Peace in the Construction of an English Teacher's Professional Identity -- Seeking Connection through Difference: Finding the Nexus of Transformative Learning, Peacebuilding and Language Teaching -- Section III: Applying Peacebuilding for Intercultural and International Peace -- 8 Can Foreign Languages Be Taught for Peace at US Government Institutes? -- 9 International Faculty and International Students in Universities: Their Roles in Fostering Peace across Languages and Cultures -- 10 Promoting Peace through Social Justice Pedagogies for Students from Immigrant Muslim Communities: Using Critical Language Awareness in Second Language Classrooms -- Section IV: Applying Peacebuilding through Positive Psychology, Peace Linguistics and Peace Language -- 11 Acting Locally to Integrate Positive Psychology and Peace: Practical Applications for Language Teaching and Learning -- 12 From Hate Speech to Empathy: Lessons for Language Educators and Society -- 13 Applying Peace Linguistics: What Peacebuilders Can Learn from the Languages of Hurt, Hate and Harm -- 14 Exploring Peace Language: Hope, Help and Harmony -- Section V: Moving Further with Peacebuilding -- 15 Peacebuilding through Classroom Activities: Inner, Interpersonal, Intergroup, Intercultural, International and Ecological Peace -- 16 Conclusion: Integrating Peace Concepts, Personal Insights and Future Peace Directions -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 28, 2020).
JSTOR
Keywords: Peace -- Study and teaching -- Activity programs; English language -- Study and teaching -- Foreign speakers -- Activity programs; Paix -- Étude et enseignement -- Méthodes actives; LANGUAGE ARTS & DISCIPLINES / Study & Teaching; English language -- Study and teaching -- Foreign speakers; Peace -- Study and teaching -- Activity programs